GAMBARAN DIMENSI KEPUASAN PELANGGAN PERUSAHAAN JASA EKSPEDISI SICEPAT - Kusumah, Intan Fazria; Wibowo, Lili Adi; Purnama, Ridwan (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to determine the effect ofÂ Service Innovation Â on Customer SatisfactionDesign / methodology / approach - This research was conducted in less than 1 year period, the research design is cross-sectional design. The method used is explanatory survey, and population 203 employees. The analysis technique used is descriptive, the questionnaire is used as a research instrument to collect data from respondents.Findings - based on the results of the study using simple linear regression analysis, the result that there is a positive influence of service innovation on customer satisfaction.Originality / value - this study provides a basis for find out the impact of service innovation on customer satisfaction.. The difference of this study with previous research is on the objects, variables, theories and the references.